ØªÙ†Ù...ÙŠØ© Ù...Ù‡Ø§Ø±Ø© Ø§Ù"Ø·Ù"Ø¨Ø© ÙÙŠ Ø§Ù"Ø¥Ù†Ø´Ø§Ø¡ Ø¨Ø§Ù"ØµÙˆØ± Ø§Ù"Ù...ØªØ³Ù"Ø³Ù"Ø© - Azizah Azizah (Universitas Islam Negeri Ar-Raniry, 2014)
The material of composing lesson (insyÄâ€™) was important for fifth grade students at Al-Manar boarding school to study. However, most students were bored and less motivated to participate in the class. The main cause of this problem is due to the traditional methods used by teachers. They did not use various medias in instructional process, besides there is no handbook. Moreover, the problem faced by the teacher in this teaching learning process was the studentsâ€™ motivation. They feel bored with traditional methods used by teachers, and some students do not understand the meaning of words taught. It caused by their lackness in mastering vocabularies and Arabic grammar skills (qawÄâ€™id). Based on the problem above, this research implements picture series to develop studentsâ€™ abilities in instructional process of composing lesson. The method used in this study was experimental study. The result of the study shows that the development of studentsâ€™ abilities in Arabic composition by using picture series was very effective. It also has positive impact in encouraging them to enjoy the teaching and learning process. Keywords: Composition; Picture Series; Instructional Media